2014
DOI: 10.1039/c3tc32231a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient spectral conversion from visible to near-infrared in transparent glass ceramics containing Ce3+–Yb3+codoped Y3Al5O12nanocrystals

Abstract: Transparent glass ceramics containing Ce 3+ -Yb 3+ codoped Y 3 Al 5 O 12 nanocrystals were prepared, and their microstructures were characterized by X-ray diffraction and transmission electron microscopy. Intense near-infrared emission at around 1000 nm, attributed to the 2 F 5/2 / 2 F 7/2 transition of Yb 3+ , was observed upon excitation at 452 nm. Efficient energy transfer from Ce 3+ ions to Yb 3+ ions was confirmed by the luminescence spectrum and fluorescent lifetime measurements; the mechanism was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…As shown in Fig. 8(b), the violet emission at 400 nm is attributed to the 5d-2 F 7/2 transition in Ce 3 þ ion [28]. One might consider the emission at 400 nm to be due to the mixture of Ce 3 þ and host material emissions.…”
Section: Pl Analysismentioning
confidence: 93%
“…As shown in Fig. 8(b), the violet emission at 400 nm is attributed to the 5d-2 F 7/2 transition in Ce 3 þ ion [28]. One might consider the emission at 400 nm to be due to the mixture of Ce 3 þ and host material emissions.…”
Section: Pl Analysismentioning
confidence: 93%
“…One effort has been made is to choose Ce 3þ ,Yb 2þ and Eu 2þ as energy donors for Yb 3þ to achieve broadband NIR quantumcutting, as these ions have strong absorption intensity in the ultraviolet-blue spectra region due to the dipole-allowed 4fe5d transitions. The efficient broadband DC has been demonstrated in Ce 3þ -Yb 3þ co-activated oxyfluoride glass [7] and glass ceramics containing YAG nanocrystals [8], Yb 2þ -Yb 3þ system in CaAl 2 O 4 phosphors [9] and Eu 2þ -Yb 3þ co-doped borate glasses [10], silicate glasses [11] and glass ceramics containing CaF 2 nanocrystals [12].…”
Section: Introductionmentioning
confidence: 98%
“…Z 3 and A 2 ? Z 2 respectively [41]. It is concluded that the fluorescence is due to a strong interaction of Yb (0.003 M) ions doped in the covalent host lattice (YAG).…”
Section: Morphologymentioning
confidence: 95%
“…Once Yb 3? ions located at YAG lattices, the 2 F 7/2 energy level splits into four Stark levels (Z 1 , Z 2 , Z 3 and Z 4 levels) and the 2 F 5/2 energy level splits into 3 Stark levels (A 1 , A 2 and A 3 levels) due to the electrostatic interaction [41]. The main Yb 3?…”
Section: Morphologymentioning
confidence: 99%